Topography-Based Removal of Corneal Epithelium for Keratoconus: A Novel and Customized Technique. Issue 7 (July 2018) - Shetty, Rohit; Vunnava, KrishnaPoojita; Khamar, Pooja; Choudhary, Urvija; Sinha Roy, Abhijit
Abstract : Purpose: To report 3 cases of management of keratoconus with a novel topography-based removal of corneal epithelium in keratoconic eyes combined with corneal crosslinking. Methods: Case report and technique description. Results: Three eyes were imaged with the Sirius topographer (Schwind Eye-Tech-Solutions, Germany). Single-step transphototherapeutic keratectomy was performed. After removal of epithelium with laser, 4-mm diameter ablation was performed centered at the location of the maximum anterior tangential curvature point. An ellipsoid ablation pattern was used for all eyes. The stromal ablation depth did not exceed 25 μm. Next, epithelium over the remaining central 8-mm cornea was manually scraped. Accelerated crosslinking (9 mW/cm 2 for 10 min) of the central 8-mm cornea was performed. After 3 months, spherical equivalent, maximal anterior curvature, and root mean square of higher-order aberrations decreased by 1.75 D, 2.0 D, and 0.15 μm, respectively, in the first eye. The spherical equivalent, maximal anterior curvature, and root mean square decreased by 2.75 D, ∼4.0 D, and 0.36 μm, respectively, in the second eye. In the third eye, the decrease was 0.75 D, 8.3 D, and 1.0 μm, respectively. After 3 months, improvement in visual acuity was significant in 2 of the 3 eyes. In 1 eye, there was a slight reduction in corrected distance visual acuity mostly because of ongoing remodeling of the cornea and delayed vision stabilization. Conclusions: A novel technique named topography-based removal of corneal epithelium in keratoconic eyes was described. This combined technique ablated less stroma and achieved outcomes comparable to those of existing techniques. Abstract : Supplemental Digital Content is Available in the Text.